Long‐Term Results in Recipients of Combined HLA‐Mismatched Kidney and Bone Marrow Transplantation Without Maintenance Immunosuppression. Issue 7 (5th June 2014) - Kawai, T.; Sachs, D. H.; Sprangers, B.; Spitzer, T. R.; Saidman, S. L.; Zorn, E.; Tolkoff‐Rubin, N.; Preffer, F.; Crisalli, K.; Gao, B.; Wong, W.; Morris, H.; et al.
<x xml:space="preserve">Abstract</x> We report here the long‐term results of HLA‐mismatched kidney transplantation without maintenance immunosuppression (IS) in 10 subjects following combined kidney and bone marrow transplantation. All subjects were treated with nonmyeloablative conditioning and an 8‐ to 14‐month course of calcineurin inhibitor with or without rituximab. All 10 subjects developed transient chimerism, and in seven of these, IS was successfully discontinued for 4 or more years. Currently, four subjects remain IS free for periods of 4.5–11.4 years, while three required reinstitution of IS after 5–8 years due to recurrence of original disease or chronic antibody‐mediated rejection. Of the 10 renal allografts, three failed due to thrombotic microangiopathy or rejection. When compared with 21 immunologically similar living donor kidney recipients treated with conventional IS, the long‐term IS‐free survivors developed significantly fewer posttransplant complications. Although most recipients treated with none or two doses of rituximab developed donor‐specific antibody (DSA), no DSA was detected in recipients treated with four doses of rituximab. Although further revisions of the current conditioning regimen are planned in order to improve consistency of the results, this study shows that long‐term stable kidney allograft survival without maintenance IS can be achieved following transient mixed chimerism induction.